WOMEN AND RELIGIOUS DISCOURSE IN THE ARAB VISION 2030 - Eka Laila Fithrianita (MISBAH : Jurnal Pendidikan dan Pemikiran Islam, 2026)
The social transformation that has taken place in Saudi Arabia through the implementation  of Vision 2030 has brought about significant changes in religious, state, and gender relations, as well as opening up space for a reinterpretation of the role of women in contemporary Islamic discourse. This study aims to analyze how Vision 2030 encourages the reconstruction of women's roles through the Islamic feminism approach and identifies the negotiation dynamics between the state reform agenda and conservative religious authorities. The research uses a qualitative method with an interdisciplinary approach that integrates Islamic feminism, hermeneutics to Qur'anic texts, especially QS. An-Nisā' [4]:34, as well as public policy analysis. Data were obtained through a literature study of academic literature, Saudi Arabian government policy documents, and works by Islamic feminism thinkers. The results of the study show that Vision 2030 not only serves as an economic diversification agenda, but also as a political instrument that encourages the reinterpretation of religious norms regarding gender relations. Policy reforms, such as the lifting of the driving ban for women, the expansion of women's participation in the public sector, and the relaxation of the male guardianship system, reflect the state's efforts to build a more inclusive religious framework through the use of Islamic feminism discourses. However, the process still faces resistance from conservative clerics who maintain a patriarchal religious interpretation rooted in the tradition of Wahhabism. This study concludes that the transformation of the role of women in Saudi Arabia takes place dialectically through continuous negotiations between religious interpretations, the country's modernization agenda, and socio-political dynamics. These findings enrich the study of religious, gender, and political relations in contemporary Muslim societies that are undergoing a process of reform.